PENGARUH INTELLECTUAL CAPITAL, SUSTAINABILITY REPORT, DAN KUALITAS LABA TERHADAP INTELLECTUAL CAPITAL DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - AYU, FILDA PUSPITA; GUSTINA, IRA; YUSRIWARTI, YUSRIWARTI; ROSLIANA, ROSLIANA (Fakultas Ekonomi Universitas Islam Indragiri, 2025)
The study aims to determine the effect of Intellectual Capital, Sustainability Report, and Profit Quality on Firm Value with GCG as a moderator in Manufacturing Companies listed on the IDX 2020-2022. The population of this study is Manufacturing Companies listed on the IDX. The sample selection uses purposive sampling. Data analysis methods include Multiple Linear Regression and Moderate Regression Analysis (MRA) using SPSS 26. Partial test results indicate that intellectual capital influences Firm Value, Sustainability Report does not influence Firm Value, and Profit Quality does not influence Firm Value. The MRA test shows that GCG strengthens the influence of intellectual capital on Firm Value, GCG weakens the influence of Sustainability Report on Firm Value, and GCG weakens the influence of Profit Quality on Firm Value.